Evidence of Frequency of Autonomic Dysfunction in Patients presenting with Tetanus in Urban and Rural population. Experience at Tertiary Care Hospital of Sind. - Meraj Fatima1, Aijaz Ali2, Awais Bashir Larik3, Ameet Jesrani4, Kiran Waqar5, Dileep Kumar6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2020)
Objective: To determine the frequency of autonomic dysfunction in patients presenting with tetanus. Design: Descriptive cross sectional study Patients and Methods: This study was conducted in department of Neurology, Jinnah Postgraduate Medical Centre, Karachi. Total 105 patients of both genders, age 20-60 years, having diagnosed of tetanus since at least 5 days were consecutively selected. Comatose patient or with history of drug reaction, sepsis, encephalitis/ meningitis, epilepsy or electrolytes imbalance were excluded. Mean + SD, frequencies & percentages were calculated. Chi-square was applied with a P value <0.05 taken as significant. Results: Frequency of autonomic dysfunction among patients of tetanus was 37.14% (n = 39). The stratification analysis showed that frequency of autonomic dysfunction was significantly (P value= 0.027) more in younger, rural living (P value 0.030) & those with a longer history of tetanus (P value = 0.001). Conclusion: One out of every three tetanus patlents was affected. Younger age, rural patients & late presenters had higher incidence of autonomic dysfunction.